2019
DOI: 10.1111/joor.12770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise therapy on painful temporomandibular disorders

Abstract: Summary Temporomandibular disorders (TMD) are common chronic musculoskeletal pain conditions among orofacial pain. Painful TMD condition such as myalgia and arthralgia can be managed by exercise therapy. However, as it is hard to access actual effect of each modality that is included in an exercise therapy programme due to multiple choice of the management modality, their efficacy remains controversial. Therefore, this review focused on the effects of exercise therapy for the management of painful TMD. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 48 publications
1
54
0
4
Order By: Relevance
“…Although clinical protocols for interventions and control groups vary, randomised clinical trials (RCTs) of jaw mobilisation or stretching exercises for TMD muscle pain suggest improvements in pain and jaw mobility compared with education and trans-cranial direct current stimulation, as well as improvements in pain compared with stabilisation splint 77 . RCTs of postural exercises suggest improvements in TMD muscle pain and jaw mobility compared with education and CBT 77 . For TMD joint pain, RCTs of jaw mobilisation or stretching exercises suggest improvements in pain and jaw mobility compared with no treatment and stabilisation splint 77 .…”
Section: Physical Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Although clinical protocols for interventions and control groups vary, randomised clinical trials (RCTs) of jaw mobilisation or stretching exercises for TMD muscle pain suggest improvements in pain and jaw mobility compared with education and trans-cranial direct current stimulation, as well as improvements in pain compared with stabilisation splint 77 . RCTs of postural exercises suggest improvements in TMD muscle pain and jaw mobility compared with education and CBT 77 . For TMD joint pain, RCTs of jaw mobilisation or stretching exercises suggest improvements in pain and jaw mobility compared with no treatment and stabilisation splint 77 .…”
Section: Physical Therapymentioning
confidence: 99%
“…RCTs of postural exercises suggest improvements in TMD muscle pain and jaw mobility compared with education and CBT 77 . For TMD joint pain, RCTs of jaw mobilisation or stretching exercises suggest improvements in pain and jaw mobility compared with no treatment and stabilisation splint 77 . Combinations of jaw strengthening and coordination exercises, and mobilisation and postural exercises improved joint pain and jaw mobility compared with education and stabilisation splint 77 .…”
Section: Physical Therapymentioning
confidence: 99%
“…The dentist is a qualified professional capable to identify and treat TMD providing this technique as a regular procedure and solution within many others that are available like pharmacologic, intra-oral appliances, physiotherapy with the use for example of Transcutaneous Electrical Nerve Stimulation (TENS) or even acupuncture. [42][43][44][45] Acupuncture, for example, is a technique considered to be capable of stimulating the regulatory systems of the organism, such as the central and peripheral nervous system, the endocrine system and the immunological system. 46 Beneath the surface, acupuncture needles engage collagen fibers, the connective tissue matrix, nerve endings, and vessels.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies have examined the effects of Rocabado's 6 × 6 exercise programme combined with another exercise programme. In TMDs, not only the TMD and masticatory muscles but also the neck and related tissues are affected, and the benefits of postural exercises have previously been reported 6‐11 . Therefore, we investigated the effect of Rocabado's 6 × 6 exercises and postural exercises combined with ICT on TMDs.…”
Section: Introductionmentioning
confidence: 98%
“…In Shimada's review, the following types of exercises used to treat TMDs were assessed: mobilisation exercises, muscle strengthening exercises (resistance training), coordination exercises and postural exercises 9 . Similarly, in a systematic review of 7 studies that investigated therapeutic exercises for TMDs, which included stretching, relaxation, coordination, strengthening and endurance exercises, Moraes et al found the exercises to be effective for the treatment of ‘muscular TMD’ 10 .…”
Section: Introductionmentioning
confidence: 99%